Analysis of Risk Factors for Low Birth Weight Babies (LBW) in the Working Area of RSU Bahteramas Southeast Sulawesi - La Ode Muhammad Ady Ardyawan; Alwahab Alwahab; Dwi Anggriani; Wa Ode Gustiani Purnamasari (International Journal of Science Technology and Health, 2024)
This study aims to analyze the risk factors for LBW events at Bahteramas General Hospital in Southeast Sulawesi in 2020. This type of research is an analytic descriptive study with a case-control design. This research was conducted at Bahteramas General Hospital in Southeast Sulawesi in 2020. This research was conducted to collect secondary data, namely patient medical records. The sample in this study were mothers who gave birth to LBW babies, and the control sample in this study were mothers who gave birth to babies who were not LBW, with a total sample of 136 samples consisting of 68 case samples and 68 control samples. Data were analyzed using the Odds Ratio test. The results of this study showed that maternal age was a risk factor for LBW with OR = 3,16 (1,57-6,90; 95%), maternal parity was a risk factor with OR = 2,07 (1,00-4,25; 95%), and petting is also a risk factor for LBW with OR = 5,03 (1,05-24,24; 95%). Maternal age, maternal parity, and obesity are risk factors for LBW events in the Working Area of RSU Bahteramas, Southeast Sulawesi, in 2020.